EVALUASI IMPLEMENTASI PROGRAM BANTUAN OPERASIONAL PENYELENGGARAAN PENDIDIKAN ANAK USIA DINI - Erfy Melany Lalupanda (Universitas Negeri Malang, 2019)
Abstract: The purpose of this study is to evaluate the implementation of the Operational Cost Program for the Implementation of Early Childhood Education (BOP PAUD). Evaluation research uses the Discrepancy model, which measures the gap between the process of implementing the BOP PAUD fund program and the procedures stipulated in Regulation of the Minister of Education and Culture Number 2 of 2016 concerning Technical Guidelines for the Use of Operational Funds for the Implementation of Early Childhood Education. Evaluation based on the design of the implementation of the BOP PAUD program process, includes: planning, implementation and accountability. The approach in this study is descriptive qualitative with interview data collection techniques and document studies in the form of School Activity and Budget Plans and Accountability Reports. The results of the study, namely: there is a gap in the implementation of the BOP PAUD program in the planning process, channeling of funds, and reporting of fund accountability. The cause of the gap is that BOP PAUD fund managers have not followed the system regulated in financing management.   Abstrak: Tujuan penelitian ini adalah untuk mengevaluasi implementasi program Biaya Operasional Penyelenggaraan Pendidikan Anak Usia Dini (BOP PAUD). Penelitian evaluasi menggunakan model Discrepancy, yaitu mengukur kesenjangan antara proses implementasi program dana BOP PAUD dengan prosedur yang telah diatur dalam Permendikbud Nomor 2 tahun 2016 tentang Petunjuk Teknis Penggunaan Dana Bantuan Operasional Penyelenggaraan Pendidikan Anak Usia Dini. Evaluasi berdasarkan desain implementasi program BOP PAUD tahap proses (process), meliputi: perencanaan, pelaksanaan dan pertanggungjawaban. Pendekatan dalam penelitian ini adalah deskriptif kualitatif dengan teknik pengumpulan data wawancara dan studi dokumen berupa Rencana Kegiatan dan Anggaran Sekolah (RKAS) dan Laporan Pertanggungjawaban. Hasil penelitian, yaitu: ada kesenjangan pada implementasi program BOP PAUD pada proses perencanaan, penyaluran dana, dan pelaporan pertanggungjawaban dana. Penyebab kesenjangan adalah pengelola dana BOP PAUD belum mengikuti sistem yang diatur dalam manajemen pembiayaan.